2021
DOI: 10.1007/s10533-021-00760-4
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic nutrients at the interface of fresh and marine waters: flow regime changes, biogeochemical cascades and picocyanobacterial blooms—the example of Florida Bay, USA

Abstract: The availability of dissolved inorganic and organic nutrients and their transformations along the fresh to marine continuum are being modified by various natural and anthropogenic activities and climate-related changes. Subtropical central and eastern Florida Bay, located at the southern end of the Florida peninsula, is classically considered to have inorganic nutrient conditions that are in higher-than-Redfield ratio proportions, and high levels of organic and chemically-reduced forms of nitrogen. However, sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 159 publications
(166 reference statements)
0
26
0
Order By: Relevance
“…These blooms ultimately resulted in a loss of 30% of Florida Bay's seagrass (Hall et al, 1999;Durako et al, 2002) when an extended bloom resulted in extensive seagrass die-offs and associated mortalities (Glibert et al, 2009b,c). These blooms have become a reoccurring feature of Florida Bay, taking place in 1991 and frequently thereafter (Boyer et al, 1999;Phlips et al, 1999;Stumpf et al, 1999;Richardson and Zimba, 2002;Glibert et al, 2004Glibert et al, , 2009bGlibert et al, ,c, 2010 through 2018 (Glibert et al, 2021). Although not directly toxic per se, these blooms reach such dense concentrations that light attenuation is diminished, affecting other primary producers such as seagrass.…”
Section: Picocyanobacterial Hab Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…These blooms ultimately resulted in a loss of 30% of Florida Bay's seagrass (Hall et al, 1999;Durako et al, 2002) when an extended bloom resulted in extensive seagrass die-offs and associated mortalities (Glibert et al, 2009b,c). These blooms have become a reoccurring feature of Florida Bay, taking place in 1991 and frequently thereafter (Boyer et al, 1999;Phlips et al, 1999;Stumpf et al, 1999;Richardson and Zimba, 2002;Glibert et al, 2004Glibert et al, , 2009bGlibert et al, ,c, 2010 through 2018 (Glibert et al, 2021). Although not directly toxic per se, these blooms reach such dense concentrations that light attenuation is diminished, affecting other primary producers such as seagrass.…”
Section: Picocyanobacterial Hab Speciesmentioning
confidence: 99%
“…Other harmful blooms also occur with either uncharacterized toxins (e.g., undescribed Karenia species) or biomass related impacts [e.g., Synechococcus sp. blooms in Florida Bay (Glibert et al, 2009b(Glibert et al, ,c, 2021, and Aureoumbra lagunensis D. A. Stockwell, DeYoe, Hargraves & P. W. Johnson blooms in the Indian River Lagoon (Gobler et al, 2013;Kang et al, 2015)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of organic matter in inland waters as nutrient and energy source for aquatic organisms (Yates et al 2016;Mackay et al 2020;Glibert et al 2021), in controlling light attenuation (Mayer et al 2006;Lu et al 2013), and regulating the transport and bioavailability of pollutants (Artifon et al 2018) and metals (Yamashita and Jaffé 2008) is widely acknowledged. A significant amount of organic matter in freshwater is processed in transit to coastal areas, preserved in soils and sediments or degraded by microorganisms (Brailsford et al 2019b, a).…”
Section: Introductionmentioning
confidence: 99%
“…Particleattached microorganisms are therefore in a dynamic equilibrium with dissolved compounds, from which they can uptake nutrients. These biotic interactions that occur in the water column likely play a central role in nutrient cycling (Simon et al 2002;Amalfitano et al 2017;Glibert et al 2021). Recently, Attermeyer et al (2018) suggested that the partial loss of dissolved organic carbon (DOC) in rivers is due to remineralisation by suspended particleattached microbes.…”
Section: Introductionmentioning
confidence: 99%